Kepatuhan Perawat Melakukan Assessment Resiko Jatuh Dengan Pelaksanaan Intervensi Pada Pasien Resiko Jatuh - Nurhayati, Susi; Rahmadiyanti, Merlinda; Hapsari, Shindi (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2020)
Nurses must have full awareness to carry out the risk of falling risk with the knowledge they have and to be obedient in carrying out these activities in order to reduce unwanted events. Objective: To determine the nurse's compliance with the risk of falling with the implementation of an intervention in the patient's risk of falling in the inpatient room. Research methods: This research is a quantitative correlation study with a cross-sectional approach. The study population was all nurses at Bhakti Wira Tamtama Hospital Semarang, with a total of 50 nurses in inpatient care. The sampling technique used was simple random sampling with 44 respondents. Results: The majority of respondents complied to conduct a fall risk assessment (81.8%), the majority of respondents intervened in a fall risk patient (84.1%). There is compliance with nurses conducting a fall risk assessment by implementing interventions on patients' risk of falling in the inpatient room with a p-value of 0,0001. Conclusion: Compliance in falling risk assessment and implementing intervention of falling risk patients by nurses will reduce the incidence of falling patients.Â Keywords: compliance of assessment; risk of falling; intervention actionÂ